Effect of the ratio of two nanosize parameters on the phase transformations. (May 2018) - Levitas, Valery I.
Abstract: We review findings obtained within an advanced Ginzburg-Landau theory that the ratio of two nanoscale parameters (e.g., width of two different interfaces or width of the interface and the Burgers vector of interfacial dislocations) drastically affects transformation nano and macroscale behavior. The ratio of two nanoscale lengths induces new phenomena, changes transformation parameters and mechanisms, and should be considered as a new dimension in a "phase diagram." Examples include surface-induced melting of nanoparticles and martensitic transformations, solid-solid transformation via an intermediate phase, and interaction between phase interface and dislocations.